Sentiment Analysis of Indonesian Society Toward the Launch of iPhone 16 Using Naive Bayes, Random Forest, and KNN Algorithms - Christopher Ezra Manurung; Hendra Mayatopani (Penerbit Jurnal Indonesia, 2025)
The development of smartphone technology, especially involving global brands like Apple, always attracts the attention of the world, including Indonesia. Every time Apple launches a new product, the public's response, particularly in Indonesia, often appears in the form of tweets on the social media platform Twitter, now known as X, which can be analyzed to reflect public views. This phenomenon presents an opportunity to understand how products are received in today's market. The dataset used in this study was obtained from tweets or comments from the Indonesian public between October and November 2024. The study found that 51.49% of the tweets fell into the positive sentiment category, 28.15% were neutral, and 20.35% were negative. Accuracy evaluation using three algorithms showed that Random Forest had the highest accuracy at 72.4%, followed by KNN with an accuracy of 66.9%, and Naïve Bayes with an accuracy of 66.3%. The results of this study indicate that the majority of the Indonesian public showed a positive sentiment toward the launch of the iPhone 16, reflecting high enthusiasm for the product. Furthermore, the Random Forest algorithm proved to be more effective in sentiment classification compared to KNN and Naïve Bayes, with higher accuracy.